Pengaruh manajemen modal kerja terhadap profitabilitas pada usaha kecil dan menengah di Indonesia - FARAH MARGARETHA; CINDY OKTAVIANI (Jurnal Bisnis dan Akuntansi, 2016)
This study aims to determine the effect of the components of working capital management, which consists of cash conversion cycle, days in account receivable period, days of inventory, and days in account payable period for profitability measured by return on asset, return on equity and gross operating profit. The sample used in this research includes 42 SMEs that ever listed on PEFINDO25 index 2009-2014. The results showed that there was a negative effect from cash conversion cycle on return on assets and a positive effect on return on equity. The components of working capital include days in accounts receivable period positively affect return on assets and return on equity, while days of inventory negatively affect return on assets and a positive effect on return on equity and gross operating profit, and days in accounts payable period positively affect gross operating profit. Meanwhile leverage have negative effect on gross operating profit. While size does have positive effect to the profitability. These results indicate that the company's managers and investors need to pay attention to the cash conversion cycle, days in accounts receivable period, days of inventory, accounts payable days in period leverage and size to increase profitability in SMEs. In addition, the government can also provide credit policy and creating a business environment conducive to SMEs.